2007
DOI: 10.1111/j.1462-5822.2006.00775.x
|View full text |Cite
|
Sign up to set email alerts
|

Co-ordinate action of bacterial adhesins and human carcinoembryonic antigen receptors in enhanced cellular invasion by capsulate serum resistant Neisseria meningitidis

Abstract: Neisseria meningitidis (Nm) is a human specific opportunistic pathogen that occasionally penetrates mucosal barriers via the action of adhesins and invasins and evades host immune mechanisms during further dissemination via capsule expression. From in vitro studies, the primary adhesion of capsulate bacteria is believed to be mediated by polymeric pili, followed by invasion via outer membrane adhesins such as Opa proteins. As the latter requires the surface capsule to be down-modulated, invading bacteria would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 46 publications
4
31
0
Order By: Relevance
“…In accordance with our previous observations and those of others for a variety of cell types expressing CEACAM1 (with constitutive expression as well as transfected or stimulated to express the receptor) (2,3,32,40,44), N. meningitidis variants expressing Opa proteins adhered in significantly greater numbers to CEACAM1-expressing T cells than did Opa Ϫ variants. Prior to this study, no formal demonstration of Opa-expressing N. meningitidis adhesion to T cells had been performed.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with our previous observations and those of others for a variety of cell types expressing CEACAM1 (with constitutive expression as well as transfected or stimulated to express the receptor) (2,3,32,40,44), N. meningitidis variants expressing Opa proteins adhered in significantly greater numbers to CEACAM1-expressing T cells than did Opa Ϫ variants. Prior to this study, no formal demonstration of Opa-expressing N. meningitidis adhesion to T cells had been performed.…”
Section: Discussionsupporting
confidence: 92%
“…Such an effect may involve localization of LR to lipid rafts (33), structures that have been implicated in invasion of host cells by a growing number of viral and bacterial pathogens (34). Our finding that upregulation of LR on the surface of eukaryotic cells is required for adherence is consistent with the need for increased expression of carcinoembryonic antigen-related cell adhesion molecules (CEACAMs) to demonstrate binding by Opa proteins (32). Inflammation during the bacteremic phase of disease prior to onset of meningitis is likely to be important for upregulating LR prior to its interaction with bacteria.…”
Section: Discussionsupporting
confidence: 77%
“…The interaction with LR is likely to complement the numerous other ligand-receptor interactions used by these bacteria and may act synergistically with them to promote adherence and invasion (32). Such an effect may involve localization of LR to lipid rafts (33), structures that have been implicated in invasion of host cells by a growing number of viral and bacterial pathogens (34).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the Opa proteins may act in synergism with the type IV pilus-mediated adhesion to ensure bacterial invasion in epithelial cells (26). A large number of Opa receptors, i.e., the CEACAM family receptors, is critical for Opa-CEACAM interaction in a capsulated background.…”
Section: Figmentioning
confidence: 99%